ANTIBACTERIAL ACTIVITY OF 50% AND 96% ETHANOL EXTRACT OF HORN BANANA PEEL (Musa acuminata x Musa balbisiana) AGAINST Propionibacterium acnes - Vanisa Al Maghfiro; Nuri; Aliyah Purwanti (LPPM Universitas dr. Soebandi, 2025)
Propionibacterium acnes is the main bacterium responsible for acne, with over 50% of its strains resistant to synthetic drugs. Treatment with natural substances, such as horn banana peel extract, can be an alternative. The polarity of the solvent, influenced by ethanol concentration, affects the compounds extracted and their antibacterial activity. This study aims to identify secondary metabolite compounds in 50% and 96% ethanol extracts of horn banana peel, evaluate the antibacterial activity of both extracts against Propionibacterium acnes, and determine the differences in antibacterial activity based on variations in solvent concentration. The banana peel extract was obtained using the Microwave Assisted Extraction (MAE) method. Phytochemical screening was conducted using the tube test method. Antibacterial activity was assessed using the well diffusion method. The 50% ethanol extract of horn banana peel had a higher yield (16,12%) compared to the 96% ethanol extract (10,02%). Both extracts contained active compounds such as alkaloids, flavonoids, tannins, polyphenols, and saponins. The 50% ethanol extract at concentrations of 5%, 10%, and 15% exhibited greater antibacterial activity against Propionibacterium acnes, with average inhibition zones of 18,68±1,32 mm, 14,11±0,35 mm, and 11.07±0.32 mm, respectively. In contrast, the 96% ethanol extract showed average inhibition zone diameters of 15,17±1,33 mm, 11,35±0,92 mm, and 8,06±0,86 mm. The differences in antibacterial activity are believed to be due to the varying polarities of the two solvents, with 50% ethanol being the more polar solvent. Two-way ANOVA analysis revealed a significant difference between the two factors (ethanol concentration and extract concentration) concerning the inhibition zones (p-value 0,004). The results indicate that both 50% and 96% ethanol extracts of horn banana peel contain secondary metabolite compounds such as alkaloids, flavonoids, tannins, polyphenols, and saponins. Both extracts exhibit antibacterial activity against Propionibacterium acnes, with a significant difference in activity between the 50% and 96% ethanol extracts.